Sensory Evaluation of Mayonnaise Preparred with Vegetable Oil and Egg Yolk of Local Chicken - Firman Jaya; Dedes Amertaningtyas; Heli Tistiana (Faculty of Animal Science Universitas Brawijaya, 2013)
The objectives of current research were to find out the precise combination between concentrations of vegetable oils (65%; 70%; 75%) and chicken egg of local chicken (6%; 9% and 12%) which produced mayonnaise with an acceptance of panelist. The results showed that the best treatment obtained from a combination of vegetable oil 75% concentration by concentration of chicken egg of local chicken 9% Key words: fat, fatty acids, carotene, shrimp waste